A Nomogram for Predicting the Risk of Radiotherapy-Related Esophageal Fistula in Esophageal Cancer Patients - Gui, Zhongxuan; Liu, Huiquan; Shi, Weijiong; Xu, Yuechen; Qian, Han; Wang, Fan (Frontiers in Oncology, 2022)
Background: To construct and validate a nomogram for predicting the risk of esophageal fistula (EF) in esophageal cancer (EC) patients receiving radiotherapy. Methods: A retrospective nested case-control study was performed, in which a total of 81 EF patients and 243 controls from 2014 to 2020 in the First Affiliated Hospital of Anhui Medical University were enrolled. Factors included in the nomogram were determined by univariate and multiple logistic regression analysis. The following methods including receiver operating characteristic (ROC) curve, C-index, calibration curves and Brier score were adopted to evaluate this nomogram. Results: Multivariate logistic regression analysis showed that T4 stage, level 4 stenosis, ulcerative EC, prealbumin, maximum diameter of GTV and NLR were the independent risk factors of EF. Accordingly, a nomogram incorporating the aforementioned six parameters was constructed. The area under the ROC curve (AUC) was 0.848 (95%CI 0.901-0.895), indicating a high prediction accuracy of this nomogram. Further evaluation of this model showed that the C-index was 0.847, while the bias-corrected C-index after internal validation was 0.833. The Brier score was 0.127. The calibration curves presented well concordance and the DCA revealed promising clinical application. Conclusions: The nomogram presents accurate and applicable prediction for the EF risk in EC patients receiving radiotherapy.